Phagocyte-like NADPH oxidase (Nox2) promotes activation of p38MAPK in pancreatic ß-cells under glucotoxic conditions: Evidence for a requisite role of Ras-related C3 botulinum toxin substrate 1 (Rac1) - Sidarala, V.; Veluthakal, R.; Syeda, K.; Vlaar, C.; Newsholme, Philip; Kowluru, A. (Elsevier Inc., 2015)
It is well established that glucotoxicity (caused by high glucose concentrations; HG) underlies pathogenesis of islet dysfunction in diabetes. We have recently demonstrated that Nox2 plays a requisite role in the generation of reactive oxygen species (ROS) under HG conditions, resulting in mitochondrial dysregulation and loss of islet ß-cell function. Herein, we investigated roles of Nox2 in the regulation of downstream stress kinase (p38MAPK) activation under HG conditions (20. mM; 24. h) in normal rodent islets and INS-1 832/13 cells. We observed that gp91-ds-tat, a specific inhibitor of Nox2, but not its inactive analog, significantly attenuated HG-induced Nox2 activation, ROS generation and p38MAPK activation, thus suggesting that Nox2 activation couples with p38MAPK activation. Since Rac1, is an integral member of the Nox2 holoenzyme, we also assessed the effects of Rac1 inhibitors (EHT 1864, NSC23766 and Ehop-016) on HG-induced p38MAPK activation in isolated ß-cells. We report a significant inhibition of p38MAPK phosphorylation by Rac1 inhibitors, implying a regulatory role for Rac1 in promoting the Nox2-p38MAPK signaling axis in the ß-cell under the duress of HG. 2-Bromopalmitate, a known inhibitor of protein (Rac1) palmitoylation, significantly reduced HG-induced p38MAPK phosphorylation. However, GGTI-2147, a specific inhibitor of geranylgeranylation of Rac1, failed to exert any significant effects on HG-induced p38MAPK activation. In conclusion, we present the first evidence that the Rac1-Nox2 signaling module plays novel regulatory roles in HG-induced p38MAPK activation and loss in glucose-stimulated insulin secretion (GSIS) culminating in metabolic dysfunction and the onset of diabetes.